Is Good Credit Good? State Credit Ratings and Economic Insecurity, 1996–2012. Issue 1 (10th December 2021) - Norris, Davon; Martin, Elizabeth C.
Abstract : Obtaining a good credit rating is an important financial goal for governments since good credit yields lower interest rates and signals fiscal responsibility. But what does a government's quest for better credit mean for the wellbeing of its residents? Although good credit gives governments access to cheaper borrowing to invest in socially beneficial services and infrastructure, working to obtain good credit may lead governments to act in ways that appease bondholders but are unfavorable to its residents. Using the case of state government credit ratings from 1996 to 2012, we demonstrate that increases in state credit ratings are associated with higher economic insecurity for a state's population, net of political and economic controls, as well as state and year fixed effects. We argue these findings illustrate that despite the economic rewards, good credit becomes detrimental once we consider the potential tradeoffs relative to other socially and economically meaningful relationships.